Technostress, career commitment, satisfaction with life, and work-family interaction among workers in information and communication technologies = Tecno-estrés, compromiso con la carrera, satisfacción con la vida y la interacción trabajo-familia en trabajadores de la información y tecnologías de la comunicación. - Carlotto, Mary Sandra; Wendt, Guilherme Welter; Jonest, Alice P.
Technostress occurs when individuals experience negative psychosocial effects of technology usage and also demonstrate negative valence associated with ICT use. It is composed of four dimensions (Disbelief, Fatigue, Anxiety, and Ineffectiveness), which describe two aspects of technostress (Technoanxiety and Technofatigue). This study aimed to investigate the relation between technostress dimensions, career commitment, life satisfaction, and work-family interactions among ICT professionals. Variables including gender, age and length of employment were also considered. The sample was composed of 234 Brazilian individuals. It was found that work-family and family-work conflicts were associated with increased technofatigue and technoanxiety, and decreased career resilience. Age and gender differences were also identified. These differences emphasize the role of organizations and society in what refers to reduce inequalities in workplace and to support better preventive actions.
El Tecno-estrés se produce cuando las personas experimentan efectos psicosociales negativos por el uso de la tecnología y también demuestran valencia negativa asociada con el uso de las TIC. Se compone de cuatro dimensiones (incredulidad, fatiga, ansiedad, e ineficacia) que describen dos aspectos del tecno-estrés (tecno-ansiedad y tecno-cansancio). El objetivo de este estudio fue investigar la relación entre las dimensiones del tecno-estrés, compromiso con la carrera, satisfacción con la vida y la interacción trabajo-familia entre los profesionales de las TIC. También se consideraron variables como el sexo, la edad y la antigüedad en el empleo. La muestra se compuso de 234 individuos brasileños. Se encontró que el conflicto trabajo-familia y familia-trabajo se asociaron con una mayor tecno-fatiga y tecno-ansiedad, y una menor resiliencia en la carrera. También se detectaron diferencias de edad y género, lo que enfatiza en el papel de las organizaciones y la sociedad en reducir las desigualdades en el lugar de trabajo y apoyar mejores acciones preventivas.
En Revista Actualidades en Psicología, Vol. 31, no. 122 (2017)
Descripción basada en el contenido visto el 12 de mayo, 2023.
Keywords: TECNOLOGIA DE LA INFORMACION -- ASPECTOS PSICOLOGICOS; CALIDAD DE VIDA; EQUIDAD DE GÉNERO; ESTRES (PSICOLOGIA)